2019
DOI: 10.37358/mp.19.1.5131
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Polymeric Membranes Ultrafiltration Process on the Retention of Bentonite Suspension

Abstract: In the field of purification and treatment of waste water resulting from various domestic and industrial activities, classical methods of retention of pollutants almost can no longer eliminate their large quantities, and this signifies a problem related to the environment. Filtration membrane technology has a larger footprint in the removal of these pollutants, and their success is due to virtually the quality of the resulting water. This paper highlights the development of a wastewater ultrafiltration process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…What leads to the decrease of the quality of the water both the surface and the underground are the different mining activities, industrial and municipal, the wastewater discharge, the improper storage of the different categories of waste. For a more efficient management of water quality it is necessary to monitor it regularly [1][2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…What leads to the decrease of the quality of the water both the surface and the underground are the different mining activities, industrial and municipal, the wastewater discharge, the improper storage of the different categories of waste. For a more efficient management of water quality it is necessary to monitor it regularly [1][2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…At the same time, 14 chemical elements present in the waste water were analyzed and after determining the concentration of the heavy metals after the completion of the experiment it can be confirmed that the use of polymeric membranes is and will be a viable solution for the purpose of protecting the environment and health.Industrial areas, regardless of the intensity of their activities, generate huge quantities of wastewater that contain pollutants from the most "friendly" with the environment to the most dangerous [1][2][3][4][5][6][7][8][9][10][11]. A quite important part of the industries generates waters that have in their composition high concentrations of heavy metals, such as: chromium, nickel, cadmium, manganese, iron, lead, etc., some being retained through the purification processes of the stations thus designed, others bypassing them, being a threat to aquatic life as well as to human health [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].In addition to the conventional methods of purification, the membrane technology has several advantages because the membranes, regardless of their type, have lower costs, are easier to exploit, in addition, they offer the possibility to separate the compounds for future use [29][30][31].The application of membranes in the processes of separation of heavy metals can have a rather high efficiency, but this efficiency depends very much on the working parameters of the experiment, such as the pH of the solution, the concentration of metals in the solution, the pressures that are created over time, other added solutions, operating time, etc. [32-34].Some studies have shown a decrease in the rejection of heavy metals as the pH value decreases, which meant a decrease in the absorption of metal ions [35]…”
mentioning
confidence: 99%
“…Industrial areas, regardless of the intensity of their activities, generate huge quantities of wastewater that contain pollutants from the most "friendly" with the environment to the most dangerous [1][2][3][4][5][6][7][8][9][10][11]. A quite important part of the industries generates waters that have in their composition high concentrations of heavy metals, such as: chromium, nickel, cadmium, manganese, iron, lead, etc., some being retained through the purification processes of the stations thus designed, others bypassing them, being a threat to aquatic life as well as to human health [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…Due to the fact that water is the root of the life and the best universal solvent, it is probably the only one substance in the world that might contain the "entire periodic system" in its composition. Water quality and treatment of wastewater represent a high interest among many researches within our Region [1][2][3][4][5][6][7][8][9]. At the same time, the determination of the presences of the microelements contained in the water samples have always represented a matter of interest and subject of study [10].…”
mentioning
confidence: 99%